2000
DOI: 10.1007/pl00008876
|View full text |Cite
|
Sign up to set email alerts
|

Long distance seed dispersal by wind: measuring and modelling the tail of the curve

Abstract: The size and shape of the tail of the seed dispersal curve is important in determining the spatial dynamics of plants, but is difficult to quantify. We devised an experimental protocol to measure long-distance dispersal which involved measuring dispersal by wind from isolated individuals at a range of distances from the source, but maintaining a large and constant sampling intensity at each distance. Seeds were trapped up to 80 m from the plants, the furthest a dispersal curve for an individual plant has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
332
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(343 citation statements)
references
References 53 publications
10
332
0
1
Order By: Relevance
“…The speed of colonization remains constant and is determined by the frequency and length of rare longdistance dispersal events. This is in agreement with other models of seed dispersal (Hewitt, 1996;Ibrahim et al, 1996;Le Corre et al, 1997;Clark, 1998;Clark et al, 1999;Clark et al, 2001;Bullock and Clark, 2000;Pakeman 2001;Petit et al, 2000). The results from this study additionally show that the speed of colonization is robust to changes in the periodicity of dispersal, a barrier of seedling establishment and a staggered start of colonization.…”
Section: Scenario Effects On Colonization Speedsupporting
confidence: 93%
See 1 more Smart Citation
“…The speed of colonization remains constant and is determined by the frequency and length of rare longdistance dispersal events. This is in agreement with other models of seed dispersal (Hewitt, 1996;Ibrahim et al, 1996;Le Corre et al, 1997;Clark, 1998;Clark et al, 1999;Clark et al, 2001;Bullock and Clark, 2000;Pakeman 2001;Petit et al, 2000). The results from this study additionally show that the speed of colonization is robust to changes in the periodicity of dispersal, a barrier of seedling establishment and a staggered start of colonization.…”
Section: Scenario Effects On Colonization Speedsupporting
confidence: 93%
“…It is argued that it is better to represent dispersal by two different mechanisms so the central tendency and the tail can be varied independently (Clark, 1998;Clark et al, 1999;Pakeman, 2001). Stratified dispersal kernels have been used to simulate realistically the ecto/endozoochorous dispersal of woodland herbaceous species (Pakeman 2001); the rapid colonization of the forest herb Asarum canadense (Cain et al, 1998); the behaviour of Hieracium pilosella (Winkler and Stocklin, 2002); and the dispersal of Calluna vulgaris and Erica cinera by wind (Bullock and Clark, 2000). Simulation models based on the oak system concluded that long-distance dispersal events not only allowed for rapid expansion but they were also the most important factor determining the spatial genetic structure of maternally inherited genes (Le Corre et al, 1997;Petit et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Even though this study uses a wider scale than most previous paternity analyses of wind-pollinated trees, the data do not allow reliable estimates of the tail of the distribution, which, as suggested by the observed portion of long-distance immigrants, may extend over tens of kilometres. On the other hand, long-distance dispersal events are likely to be governed by complex stochastic atmospheric processes that are poorly predicted by standard empirical or mechanistic models (Bullock and Clarke, 2000), and they may require novel experimental and analytical approaches (Nathan et al, 2003).…”
Section: Experimental Constraintsmentioning
confidence: 99%
“…The ID model with a Gaussian dispersal kernel is essentially equivalent to the classical RD model, in a sense that will be made precise in this paper. Alternative dispersal kernels with heavier tails model the faster and wider spreading observed in many field studies (Bullock and Clarke, 2000;Clark et al, 1999Clark et al, , 2001Katul et al, 2005;Klein et al, 2006;Paradis et al, 2002). This paper proposes a new fractional RD equation…”
Section: Introductionmentioning
confidence: 97%